Phase-dependent friction of nanoconfined water meniscus. Issue 5 (2nd February 2021) - Zhao, Xin; Qiu, Hu; Zhou, Wanqi; Guo, Yufeng; Guo, Wanlin
Abstract : A direct correlation between the phase state of a nanoscale water meniscus and its friction properties is established, which may benefit the design of micro- and nano-electromechanical systems operating under ambient conditions. Abstract : A water meniscus naturally forms under ambient conditions at the point of contact between a nanoscale tip and an atomically flat substrate. Here, we study the effect of the phase state of this nanoscale meniscus—consisting of coexisting monolayer, bilayer and trilayer phase domains—on the frictional behavior during tip sliding by means of molecular dynamics simulations. While the meniscus experiences a domain-by-domain liquid-to-solid phase transition induced by lateral compression, we observe an evident transition in measured friction curves from continuous sliding to stick-slip and meanwhile a gradual increase in friction forces. Moreover, the stick-slip friction can be modulated by varying lattice orientation of the monolayer ice domain in the meniscus, choosing the sliding direction or applying in-plane strains to the substrate. Our results shed light on the rational design of high-performance micro- and nano-electromechanical systems relying on hydration lubrication.